Autosomal dominant inheritance - Holden, Simon (Henry Stewart Talks, 2021)
Autosomal dominant disorders, Genetics, Inheritance, Genetic disorders, Osteogenesis imperfecta, RASopathies, Huntington disease, Penetrance, De novo mutations